HYDROTROPIC EXTRACTION OF THEOBROMINE FROM COCOA BEAN SHELL. - I. Hartati (Universitas Wahid Hasyim, 2010)
Cocoa bean shell (CBS) is a waste product from chocolate and cocoa milling industries. CBS is high in nutritive value but it is of limited use in animal feeds because of its toxic theobromine content. Though its theobromine content limited the use of CBS, its amino acid profile of CBS compares favourably with palm kernel cake suggesting that it could be utilized as a medium protein source to substitute grain protein in livestock diets. Theobromine is also possesed many farmacological function such as anti cancer, diuretics, cardiac stimulants, hypocholesterolemic, smooth-muscle relaxants, atshma and coronary vasodilators. Considering that Indonesia is the third largest producer of cocoa in the, the potential usage of both protein and theobromine content of cocoa bean shell, thus it is neccesary to separate theobromine from cocoa bean shell. A new developed separation process is the extraction process using aqueous hydrotropes solution for recovery of naturally occurring secondary metabolites. The solubility of the secondary metabolites extracted are increased sharply and easily recovered. Recently several researches demonstrated that high solubilization capacity and selectivity in solubilization by hydrotropy could be used for extraction of water insoluble bioactive compound such as piperin, limonin, curcuminoids and forskolin. Based on the promising result by hydrotropic extraction of natural product, thus it is a promising method in administering theobromine from cocoa bean shell. Keywords: hydrotropic, extraction, theobromine, cocoa bean shell